Dynamic forecasting model for short series age-specific mortality / Wan Zakiyatussariroh Wan Husin - Wan Husin, Wan Zakiyatussariroh (Institute of Graduate Studies, UiTM, 2017)
This thesis presents results of a research in developing a model to forecast mortality using a combination of existing demographic and time series models, specifically proposing a common factor model for forecasting Malaysia mortality using the available mortality data set. This research has been motivated by three (3) factors. Firstly, the need for a mortality forecasting model “tailored” to Malaysia data set which has been borne out of the scarcity of studies in forecasting Malaysia mortality, crucial to government pensions and social security as well as to practitioners in related fields. Secondly, over the last decades, different models for forecasting mortality have been used to produce mortality projections for different countries. However, no “universal” model, applicable to all countries, has been developed, more so for short-series historical mortality data. Hence, there is a need to develop and apply an appropriate model to produce good forecasts of Malaysia mortality. Thirdly, while undertaking a literature review to gain insights into current mortality forecasting models, it became apparent that a gap existed between the current models used for forecasting and projecting Malaysia mortality and the current practice of incorporating state-space methodology in mortality forecasting models, specifically in modelling high-dimensional short series mortality data. Hence, the research gap has to be narrowed. The first objective of this research is to establish a comprehensive literature review on modeling and forecasting mortality data..